A reinforced fluorosilicone rubber composite material and preparation method thereof

By preparing the modified carbon nanotube/silica composite filler and adding it to fluorosiloxane, the problem of limited mechanical properties of reinforcement fillers in existing fluorosilicone rubber composite materials is solved, and higher mechanical properties and better molding and processing properties are achieved.

CN119285958BActive Publication Date: 2025-04-18DALIAN LISHI RUBBER IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411807192.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-18
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Among the existing fluorosilic rubber composite materials, the mechanical properties of reinforcement fillers are limited, and the large amount of addition will lead to difficulties in forming and processing.

Method used

The composite filler is prepared by preparing carbon nanotube/silica composite material and modifying the composite material with 3-mercaptopropyltriethoxysilane, and the composite material is prepared by adding polyfluorosiloxane to prepare a fluorosilicone rubber composite material to improve its mechanical properties.

Benefits of technology

It significantly improves the mechanical properties of fluorosilic rubber, including tensile strength, hardness and thermal stability, while improving the convenience of molding and processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285958B_ABST
    Figure CN119285958B_ABST
Patent Text Reader

Abstract

The invention discloses a reinforced fluorosilicone rubber composite material and a preparation method thereof in the field of rubber technology, wherein the reinforced fluorosilicone rubber composite material comprises the following components in parts by weight: 60-70 parts of methylvinylcyclotetrasiloxane, 20-30 parts of methyltrifluoropropylcyclotrisiloxane, 1-3 parts of tetramethylammonium hydroxide, 2-4 parts of benzoin dimethyl ether, 3-5 parts of 2,2-(1,2-ethylenedioxy)bis-ethylmercaptan, and 40-60 parts of composite fillers, and the composite fillers are prepared by the following components: carboxyl carbon nanotubes, tetraethyl orthosilicate, and 3-mercaptopropyltriethoxysilane. The present invention prepares a carbon nanotube / silicon dioxide composite material, and modifies the composite material by 3-mercaptopropyltriethoxysilane to obtain a composite filler, which is added to polyfluorosilicone to prepare a fluorosilicone rubber composite material to improve the mechanical properties of fluorosilicone rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber, and specifically refers to a reinforced fluorosilicone rubber composite material and a preparation method thereof. Background Art

[0002] Fluorosilicone rubber is a new material developed on the basis of organic fluorine and organic silicon, realizing the complementary advantages of organic silicon and organic fluorine materials. Since fluorosilicone rubber combines high bond energy silicon-oxygen bonds and carbon-fluorine bonds that have a shielding effect on carbon-carbon bonds, it exhibits excellent resistance to high and low temperatures, environmental aging, oil and chemical corrosion, and is an important polymer material used in various fields such as aerospace, automobiles, machinery, electronics, and chemicals. However, like ordinary silicone rubber, fluorosilicone rubber also requires a large amount of reinforcing fillers to obtain certain mechanical properties to meet its application requirements. At present, the main reinforcing filler used in fluorosilicone rubber is white carbon black, but white carbon black has limited effect on the improvement of the mechanical properties of fluorosilicone rubber, and adding a large amount will make the molding and processing of fluorosilicone rubber difficult.

[0003] The existing technology currently has the following main problems: the reinforcing filler has limited effect on improving the mechanical properties of fluorosilicone rubber, and adding a large amount of it will make the molding and processing of fluorosilicone rubber difficult. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a reinforced fluorosilicone rubber composite material and a preparation method thereof. In order to solve the problem that the mechanical properties of fluorosilicone rubber are limitedly improved by reinforcing fillers and a large amount of addition will lead to difficulties in the molding and processing of fluorosilicone rubber, the present invention prepares a carbon nanotube / silicon dioxide composite material and modifies the composite material by 3-mercaptopropyltriethoxysilane to obtain a composite filler, which is added to polyfluorosilicone to prepare a fluorosilicone rubber composite material to improve the mechanical properties of fluorosilicone rubber.

[0005] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: The present invention proposes a reinforced fluorosilicone rubber composite material and a preparation method thereof, wherein the reinforced fluorosilicone rubber composite material comprises the following components in parts by weight: 60-70 parts of methyl vinyl cyclotetrasiloxane, 20-30 parts of methyl trifluoropropyl cyclotrisiloxane, 1-3 parts of tetramethyl ammonium hydroxide, 2-4 parts of benzoin dimethyl ether, 3-5 parts of 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan), and 40-60 parts of composite filler.

[0006] The composite filler is prepared from the following components: carboxyl carbon nanotubes, ethyl orthosilicate and 3-mercaptopropyltriethoxysilane.

[0007] Furthermore, the preparation method of the composite filler comprises the following steps:

[0008] S1, weighing carboxyl carbon nanotubes and adding them to a mixed solution of isopropanol and deionized water, adding ammonia water with a concentration of 25wt%, ultrasonic treatment, adding tetraethyl orthosilicate dropwise, reacting at 45-55°C for 10-12h, washing with deionized water and ethanol by centrifugation after the reaction, drying at 70°C, and grinding into powder to obtain a carbon nanotube / silicon dioxide composite material;

[0009] S2. Weigh the carbon nanotube / silicon dioxide composite material prepared in step S1, add it to ethanol, and perform ultrasonic treatment. Under a nitrogen atmosphere, add 3-mercaptopropyltriethoxysilane, stir in a constant temperature water bath at 30° C. for 20-24 h, wash with ethanol by centrifugation after the reaction is completed, and dry at 30° C. to obtain a composite filler.

[0010] Preferably, in step S1, the amount of the carboxyl carbon nanotubes added to the mixed solution is 0.01-0.02 g / mL, and the volume ratio of isopropanol to deionized water in the mixed solution is 1:1.

[0011] Preferably, in step S1, the volume ratio of the aqueous ammonia to the mixed solution is 1-2:25.

[0012] Preferably, in step S1, the ultrasonic treatment time is 30-40 min and the power is 200 W.

[0013] Preferably, in step S1, the volume ratio of the tetraethyl orthosilicate to the mixed solution is 1-1.5:10.

[0014] Preferably, in step S2, the amount of the carbon nanotube / silicon dioxide composite material added to ethanol is 0.03-0.05 g / mL.

[0015] Preferably, in step S2, the ultrasonic treatment time is 20-30 min and the power is 200W.

[0016] Preferably, in step S2, the mass ratio of the 3-mercaptopropyltriethoxysilane to the carbon nanotube / silicon dioxide composite material is 1-3:5.

[0017] The present invention provides a method for preparing a reinforced fluorosilicone rubber composite material, which specifically comprises the following steps:

[0018] (1) Weigh methylvinylcyclotetrasiloxane and methyltrifluoropropylcyclotrisiloxane and place them in a flask, introduce nitrogen, stir in an oil bath at 80°C for 1-2 hours at a stirring speed of 300 rpm, add tetramethylammonium hydroxide after cooling, stir in an oil bath at 80°C for 6-8 hours at a stirring speed of 200 rpm, and then heat at 140°C for 10-30 minutes to remove impurities to obtain polyfluorosiloxane;

[0019] (2) Weigh the composite filler in an amount of 0.05 g / mL and add it to toluene, stir evenly to obtain liquid A; take the polyfluorosilicone prepared in step (1) and add it to toluene in an amount of 0.05 g / mL and stir evenly to obtain liquid B; mix liquid A and liquid B, add benzoin dimethyl ether and 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan), stir evenly, vacuum dry to remove toluene, perform cold isostatic pressing at a pressure of 200-300 MPa, and then react under vacuum conditions at 80-90°C for 8-12 h to obtain a reinforced fluorosilicone rubber composite material.

[0020] The beneficial effects achieved by the present invention are as follows:

[0021] The present invention uses tetraethyl orthosilicate and carboxyl carbon nanotubes to prepare a carbon nanotube / silicon dioxide composite material through an in-situ growth method, and modifies the composite material through 3-mercaptopropyl triethoxysilane to prepare a composite filler, which is added to polyfluorosiloxane prepared by using methylvinyl cyclotetrasiloxane and methyltrifluoropropyl cyclotrisiloxane as monomers to prepare a fluorosilicone rubber composite material through an addition reaction, so as to improve the mechanical properties of the fluorosilicone rubber; wherein the carbon nanotube has high strength, elastic modulus and chemical stability, and can be used as a reinforcing filler to improve the mechanical properties of the fluorosilicone rubber; the silicon dioxide prepared from tetraethyl orthosilicate has hydroxyl groups, and can be composited with the carboxyl carbon nanotubes, so as to improve the mutual bonding between the carbon nanotubes. The entanglement phenomenon can be improved, and the dispersibility of carbon nanotubes can be improved. 3-Mercaptopropyltriethoxysilane can introduce thiol groups on the surface of the composite material, thereby improving the compatibility of the composite material with the rubber matrix; methylvinylcyclotetrasiloxane and methyltrifluoropropylcyclotrisiloxane can be polymerized under the action of the initiator tetramethylammonium hydroxide to prepare polyfluorosilicone with vinyl and trifluoropropyl side chains, and benzoin dimethyl ether is used as an initiator and 2,2-(1,2-ethylenedioxy)bisethylmercaptan is used as a cross-linking agent to initiate an addition reaction between polyfluorosilicone and carbon nanotube / silica composite materials containing thiol groups, thereby improving the cross-linking density of fluorosilicone rubber and preparing high-performance fluorosilicone rubber composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The tensile strength test results of the reinforced fluorosilicone rubber composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 are shown;

[0023] Figure 2 The figure is a hardness test result diagram of the reinforced fluorosilicone rubber composite material prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2;

[0024] Figure 3 The compression permanent deformation test results of the reinforced fluorosilicone rubber composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 are shown;

[0025] Figure 4 This is a graph showing the thermal stability test results of the reinforced fluorosilicone rubber composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2;

[0026] Figure 5 This is a scanning electron microscope image of the composite filler prepared in Example 1 of the present invention.

[0027] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0030] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0031] Example 1

[0032] A reinforced fluorosilicone rubber composite material is prepared by including the following components in parts by weight: 60 parts of methylvinylcyclotetrasiloxane, 20 parts of methyltrifluoropropylcyclotrisiloxane, 1 part of tetramethylammonium hydroxide, 2 parts of benzoin dimethyl ether, 3 parts of 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan) and 40 parts of composite filler.

[0033] The composite filler is prepared from the following components: carboxyl carbon nanotubes, ethyl orthosilicate, and 3-mercaptopropyltriethoxysilane.

[0034] Furthermore, the preparation method of the composite filler comprises the following steps:

[0035] S1. Weigh 1 g of carboxyl carbon nanotubes and add them to a mixed solution of 100 mL of isopropanol and deionized water, wherein the volume ratio of isopropanol to deionized water in the mixed solution is 1:1. Add 4 mL of 25 wt% ammonia water, perform ultrasonic treatment for 30 min at a power of 200 W, drop 10 mL of ethyl orthosilicate, react at 45 ° C for 10 h, wash with deionized water and ethanol by centrifugation after the reaction is completed, dry at 70 ° C, and grind into powder to obtain a carbon nanotube / silicon dioxide composite material.

[0036] S2. Weigh 1.5 g of the carbon nanotube / silicon dioxide composite material prepared in step S1, add it to 50 mL of ethanol, and perform ultrasonic treatment for 20 min at a power of 200 W. Under a nitrogen atmosphere, add 0.3 g of 3-mercaptopropyltriethoxysilane, stir in a constant temperature water bath at 30° C. for 20 h, wash with ethanol by centrifugation after the reaction is completed, and dry at 30° C. to obtain a composite filler.

[0037] This embodiment provides a method for preparing a reinforced fluorosilicone rubber composite material, which specifically includes the following steps:

[0038] (1) Weigh methylvinylcyclotetrasiloxane and methyltrifluoropropylcyclotrisiloxane into a flask, introduce nitrogen, stir in an oil bath at 80°C for 1 h at a stirring speed of 300 rpm, add tetramethylammonium hydroxide after cooling, stir in an oil bath at 80°C for 6 h at a stirring speed of 200 rpm, and heat at 140°C for 10 min to remove impurities to obtain polyfluorosilicone;

[0039] (2) Weigh the composite filler in an amount of 0.05 g / mL and add it to toluene, stir evenly to obtain liquid A; take the polyfluorosilicone prepared in step (1) and add it to toluene in an amount of 0.05 g / mL and stir evenly to obtain liquid B; mix liquid A and liquid B, add benzoin dimethyl ether and 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan), stir evenly, vacuum dry to remove toluene, perform cold isostatic pressing at a pressure of 200 MPa, and then react at 80°C under vacuum conditions for 8 h to obtain a reinforced fluorosilicone rubber composite material.

[0040] Example 2

[0041] A reinforced fluorosilicone rubber composite material is prepared by including the following components in parts by weight: 70 parts of methylvinylcyclotetrasiloxane, 30 parts of methyltrifluoropropylcyclotrisiloxane, 3 parts of tetramethylammonium hydroxide, 4 parts of benzoin dimethyl ether, 5 parts of 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan) and 60 parts of composite filler.

[0042] The composite filler is prepared from the following components: carboxyl carbon nanotubes, ethyl orthosilicate, and 3-mercaptopropyltriethoxysilane.

[0043] Furthermore, the preparation method of the composite filler comprises the following steps:

[0044] S1. Weigh 2 g of carboxyl carbon nanotubes and add them to a mixed solution of 100 mL of isopropanol and deionized water, wherein the volume ratio of isopropanol to deionized water in the mixed solution is 1:1. Add 8 mL of 25 wt% ammonia water, perform ultrasonic treatment for 40 min at a power of 200 W, drop 15 mL of ethyl orthosilicate, react at 55 ° C for 12 h, wash with deionized water and ethanol by centrifugation after the reaction is completed, dry at 70 ° C, and grind into powder to obtain a carbon nanotube / silicon dioxide composite material.

[0045] S2. Weigh 2.5 g of the carbon nanotube / silicon dioxide composite material prepared in step S1, add it to 50 mL of ethanol, and perform ultrasonic treatment for 30 min at a power of 200 W. Under a nitrogen atmosphere, add 1.5 g of 3-mercaptopropyltriethoxysilane, stir in a constant temperature water bath at 30° C. for 24 h, wash with ethanol by centrifugation after the reaction is completed, and dry at 30° C. to obtain a composite filler.

[0046] This embodiment provides a method for preparing a reinforced fluorosilicone rubber composite material, which specifically includes the following steps:

[0047] (1) Weigh methylvinylcyclotetrasiloxane and methyltrifluoropropylcyclotrisiloxane into a flask, introduce nitrogen, stir in an oil bath at 80°C for 2 h at a stirring speed of 300 rpm, add tetramethylammonium hydroxide after cooling, stir in an oil bath at 80°C for 8 h at a stirring speed of 200 rpm, and heat at 140°C for 30 min to remove impurities to obtain polyfluorosilicone;

[0048] (2) Weigh the composite filler in an amount of 0.05 g / mL and add it to toluene, stir evenly to obtain liquid A; take the polyfluorosilicone prepared in step (1) and add it to toluene in an amount of 0.05 g / mL, stir evenly to obtain liquid B; mix liquid A and liquid B, add benzoin dimethyl ether and 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan), stir evenly, vacuum dry to remove toluene, perform cold isostatic pressing at a pressure of 300 MPa, and then react at 90°C under vacuum conditions for 12 h to obtain a reinforced fluorosilicone rubber composite material.

[0049] Example 3

[0050] A reinforced fluorosilicone rubber composite material is prepared by including the following components in parts by weight: 65 parts of methylvinylcyclotetrasiloxane, 25 parts of methyltrifluoropropylcyclotrisiloxane, 2 parts of tetramethylammonium hydroxide, 3 parts of benzoin dimethyl ether, 4 parts of 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan) and 50 parts of composite filler.

[0051] The composite filler is prepared from the following components: carboxyl carbon nanotubes, ethyl orthosilicate, and 3-mercaptopropyltriethoxysilane.

[0052] Furthermore, the preparation method of the composite filler comprises the following steps:

[0053] S1. Weigh 1.5 g of carboxyl carbon nanotubes and add them to a mixed solution of 100 mL of isopropanol and deionized water, wherein the volume ratio of isopropanol to deionized water in the mixed solution is 1:1. Add 6 mL of 25 wt% ammonia water, perform ultrasonic treatment for 35 min at a power of 200 W, dropwise add 13 mL of ethyl orthosilicate, react at 50 ° C for 11 h, wash with deionized water and ethanol by centrifugation after the reaction is completed, dry at 70 ° C, and grind into powder to obtain a carbon nanotube / silicon dioxide composite material.

[0054] S2. Weigh 2 g of the carbon nanotube / silicon dioxide composite material prepared in step S1, add it to 50 mL of ethanol, and perform ultrasonic treatment for 25 min at a power of 200 W. Under a nitrogen atmosphere, add 0.8 g of 3-mercaptopropyltriethoxysilane, stir in a constant temperature water bath at 30° C. for 22 h, wash with ethanol by centrifugation after the reaction is completed, and dry at 30° C. to obtain a composite filler.

[0055] This embodiment provides a method for preparing a reinforced fluorosilicone rubber composite material, which specifically includes the following steps:

[0056] (1) Weigh methylvinylcyclotetrasiloxane and methyltrifluoropropylcyclotrisiloxane and place them in a flask, introduce nitrogen, stir in an oil bath at 80°C for 1.5 h at a stirring speed of 300 rpm, add tetramethylammonium hydroxide after cooling, stir in an oil bath at 80°C for 7 h at a stirring speed of 200 rpm, and heat at 140°C for 20 min to remove impurities to obtain polyfluorosilicone;

[0057] (2) Weigh the composite filler in an amount of 0.05 g / mL and add it to toluene, stir evenly to obtain liquid A; take the polyfluorosilicone prepared in step (1) and add it to toluene in an amount of 0.05 g / mL and stir evenly to obtain liquid B; mix liquid A and liquid B, add benzoin dimethyl ether and 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan), stir evenly, vacuum dry to remove toluene, perform cold isostatic pressing at a pressure of 250 MPa, and then react at 85°C under vacuum conditions for 10 h to obtain a reinforced fluorosilicone rubber composite material.

[0058] Comparative Example 1

[0059] This comparative example provides a reinforced fluorosilicone rubber composite material and a preparation method thereof, which differs from Example 1 only in that carbon nanotubes are used instead of the composite filler, and the other components and component contents are the same as those in Example 1.

[0060] Comparative Example 2

[0061] This comparative example provides a reinforced fluorosilicone rubber composite material and a preparation method thereof, which differs from Example 1 in that the preparation components of the composite filler do not include 3-mercaptopropyltriethoxysilane, the preparation method of the composite filler does not include step S2, and the remaining components and component contents are the same as those in Example 1.

[0062] 1. Tensile strength test

[0063] The tensile strength test of the reinforced fluorosilicone rubber composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-2 is carried out as follows: a universal electronic tensile testing machine is used for testing in accordance with GB / T528-2009, the specimens are cut into standard dumbbell-shaped splines with a size of 75 mm × 4 mm × 1 mm, and the tensile rate is set to 10 mm / min.

[0064] Figure 1 The tensile strength test results of the reinforced fluorosilicone rubber composite materials prepared by Examples 1-3 of the present invention and Comparative Examples 1-2 are shown in the figure. As shown in the figure, the tensile strengths of Examples 1-3 are 19.3 MPa, 20.2 MPa, and 18.7 MPa, respectively, and the tensile strengths of Comparative Examples 1-2 are 10.5 MPa and 12.8 MPa, respectively. The tensile strength of Example 1 is significantly improved compared with that of Comparative Example 1. This is because the introduction of silica can increase the dispersibility of carbon nanotubes, thereby improving the strengthening effect of carbon nanotubes on the rubber matrix. The improvement in the tensile strength of Example 1 compared with Comparative Example 2 indicates that the modification of 3-mercaptopropyltriethoxysilane can improve the compatibility of the carbon nanotube / silica composite material with the rubber matrix, thereby improving the tensile strength of the fluorosilicone rubber.

[0065] 2. Hardness test

[0066] The hardness test was carried out on the reinforced fluorosilicone rubber composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-2. The specific method is as follows: cut the samples with a size of 50 mm×50 mm×6 mm, place the samples at 25°C and 50% rh for 40 hours before testing, place the samples on the Shore A hardness tester platform to test the Shore A hardness of the samples, and keep the pressure needle 25 mm away from the sample surface. Read the data within 3 seconds after the pressure needle is completely pressed down and contacts the sample. Take 5 points on the sample and measure them at a distance of 6 mm between each point. Take the average value of the results.

[0067] Figure 2 This is a graph showing the hardness test results of the reinforced fluorosilicone rubber composite materials prepared by Examples 1-3 and Comparative Examples 1-2 of the present invention. As shown in the figure, the hardness of Examples 1-3 is 79 degrees, 80 degrees, and 78 degrees, and the hardness of Comparative Examples 1 and 2 is 65 degrees and 70 degrees.

[0068] 3. Compression set test

[0069] The reinforced fluorosilicone rubber composite materials prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention were subjected to compression set test. The specific method is as follows: Referring to GB / T7759.1-2015, the compression set rate was tested. The sample was placed in a mold and compressed to 25% of the initial height. The test conditions were 200°C × 24h. The compression set rate was calculated according to the following formula:

[0070]

[0071] Among them, h0 is the initial height of the sample; h1 is the height of the sample after recovery; h s is the height of the stopper.

[0072] Figure 3 This is a compression set test result diagram of the reinforced fluorosilicone rubber composite materials prepared by Examples 1-3 of the present invention and Comparative Examples 1-2. The compression set rates of Examples 1-3 are 13.2%, 12.6%, and 14.1%, and the compression set rates of Comparative Examples 1 and 2 are 21.7% and 18.6%.

[0073] 4. Thermal stability test

[0074] The thermal stability test of the reinforced fluorosilicone rubber composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-2 is carried out. The specific method is as follows: according to GB / T3512-2014, the cut samples are placed in an aging oven for hot air accelerated aging. The aging conditions are 200°C×48h. After the aging, the tensile strength and hardness are tested and the change rate is calculated.

[0075] Figure 4 This is a graph showing the thermal stability test results of the reinforced fluorosilicone rubber composite materials prepared by Examples 1-3 of the present invention and Comparative Examples 1-2. The tensile strength change rates of Examples 1-3 are -6.7%, -5.4%, and -6.1%, respectively, and the hardness change rates are -4.8%, -5.1%, and -4.5%, respectively. The tensile strength change rates of Comparative Examples 1 and 2 are -18.5% and -15.7%, respectively, and the hardness change rates are -10.4% and -8.8%, respectively.

[0076] 5. Scanning Electron Microscope Observation

[0077] The composite filler prepared in Example 1 was observed using a scanning electron microscope.

[0078] Figure 5 This is a scanning electron microscope image of the composite filler prepared in Example 1 of the present invention, wherein silicon dioxide is filled on the surface of the carbon nanotubes to improve the phenomenon of mutual entanglement between the carbon nanotubes.

[0079] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0080] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a reinforced fluorosilicone rubber composite material, characterized in that: The reinforced fluorosilicone rubber composite material is prepared by comprising the following components in parts by weight: 60-70 parts of methyl vinyl cyclotetrasiloxane, 20-30 parts of methyl trifluoropropyl cyclotrisiloxane, 1-3 parts of tetramethyl ammonium hydroxide, 2-4 parts of benzoin dimethyl ether, 3-5 parts of 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan), and 40-60 parts of composite filler; the composite filler is prepared by comprising the following components: carboxyl carbon nanotubes, tetraethyl orthosilicate, and 3-mercaptopropyl triethoxysilane; The preparation method of the composite filler comprises the following steps: S1, weighing carboxyl carbon nanotubes and adding them to a mixed solution of isopropanol and deionized water, adding ammonia water with a concentration of 25wt%, ultrasonic treatment, adding tetraethyl orthosilicate dropwise, reacting at 45-55°C for 10-12h, washing with deionized water and ethanol by centrifugation after the reaction, drying at 70°C, and grinding into powder to obtain a carbon nanotube / silicon dioxide composite material; S2, weighing the carbon nanotube / silicon dioxide composite material prepared in step S1, adding it to ethanol, ultrasonically treating it, adding 3-mercaptopropyltriethoxysilane under a nitrogen atmosphere, stirring it in a constant temperature water bath at 30° C. for 20-24 hours, washing it by centrifugation with ethanol after the reaction is completed, and drying it at 30° C. to obtain a composite filler; The preparation method of the reinforced fluorosilicone rubber composite material comprises the following steps: (1) Weigh methylvinylcyclotetrasiloxane and methyltrifluoropropylcyclotrisiloxane and place them in a flask, introduce nitrogen, stir in an oil bath at 80°C for 1-2 hours at a stirring speed of 300 rpm, add tetramethylammonium hydroxide after cooling, stir in an oil bath at 80°C for 6-8 hours at a stirring speed of 200 rpm, and then heat at 140°C for 10-30 minutes to remove impurities to obtain polyfluorosiloxane; (2) Weigh the composite filler in an amount of 0.05 g / mL and add it to toluene, stir evenly to obtain liquid A; take the polyfluorosilicone prepared in step (1) and add it to toluene in an amount of 0.05 g / mL and stir evenly to obtain liquid B; mix liquid A and liquid B, add benzoin dimethyl ether and 2,2-(1,2-ethylenedioxy)bis(ethyl mercaptan), stir evenly, vacuum dry to remove toluene, perform cold isostatic pressing at a pressure of 200-300 MPa, and then react under vacuum conditions at 80-90°C for 8-12 h to obtain a reinforced fluorosilicone rubber composite material.

2. The method for preparing the reinforced fluorosilicone rubber composite material according to claim 1, characterized in that: In step S1, the amount of the carboxyl carbon nanotubes added to the mixed solution is 0.01-0.02 g / mL, and the volume ratio of isopropanol to deionized water in the mixed solution is 1:

1.

3. The method for preparing the reinforced fluorosilicone rubber composite material according to claim 2, characterized in that: In step S1, the volume ratio of the ammonia water to the mixed solution is 1-2:

25.

4. The method for preparing the reinforced fluorosilicone rubber composite material according to claim 3, characterized in that: In step S1, the ultrasonic treatment time is 30-40 minutes and the power is 200W.

5. The method for preparing the reinforced fluorosilicone rubber composite material according to claim 4, characterized in that: In step S1, the volume ratio of the tetraethyl orthosilicate to the mixed solution is 1-1.5:

10.

6. The method for preparing the reinforced fluorosilicone rubber composite material according to claim 5, characterized in that: In step S2, the amount of the carbon nanotube / silicon dioxide composite material added to ethanol is 0.03-0.05 g / mL.

7. The method for preparing the reinforced fluorosilicone rubber composite material according to claim 6, characterized in that: In step S2, the ultrasonic treatment time is 20-30 minutes and the power is 200W.

8. The method for preparing the reinforced fluorosilicone rubber composite material according to claim 7, characterized in that: In step S2, the mass ratio of the 3-mercaptopropyltriethoxysilane to the carbon nanotube / silicon dioxide composite material is 1-3:5.

Citation Information

Patent Citations

  • Flexible dielectric elastomer composite material based on nanometer liquid metal and preparation method thereof

    CN109467931A

  • Silicon oxide coated carbon nano tube and preparation device, method and application thereof

    CN115466937A